Beyond political correctness : - Cummings, Michael S. (Lynne Rienner Publishers, 2001)
Arguing that too many progressives have avoided politically sensitive issues, condemning themselves to political ineffectiveness, this text urges a transformation of US culture and institutions enabling individuals to pursue vital interests without undermining the public good.